A noção de sindérese em Tomás de Aquino - Monteiro, Italo Dant Alves (2024)
This dissertation aims to clarify the following question: what is the notion of synderesis in St. Thomas Aquinas (1224/1225-1274), especially in question 79, article 12, of the Prima Pars of the Summa theologiae? This analysis allows us to draw a parallel with question 16, in 3 articles, of the Disputed Questions about truth. Synderesis appears to be a permanent disposition, a special habitus, which incites us to do good and to avoid evil. We will thus be able to understand how synderesis influences the moral conscience, present in question 17 of the Quaestiones disputatae De veritate, and how it is expressed in the natural law, present in question 94 of the Prima Secundae of the Summa theologiae. These elements provide us with the foundations of St. Thomas' moral “cathedral”, the basis for understanding the principle of moral action, prior to prudential virtue, a principle that is rooted in human rational nature, according to synderesis as a natural intellectual disposition, which allows us to know the natural moral law.